2015
DOI: 10.19173/irrodl.v16i3.2112
|View full text |Cite
|
Sign up to set email alerts
|

Massive open online course completion rates revisited: Assessment, length and attrition

Abstract: This analysis is based upon enrolment and completion data collected for a total of 221 Massive Open Online Courses (MOOCs). It extends previously reported work (Jordan, 2014) with an expanded dataset; the original work is extended to include a multiple regression analysis of factors that affect completion rates and analysis of attrition rates during courses. Completion rates (defined as the percentage of enrolled students who completed the course) vary from 0.7% to 52.1%, with a median value of 12.6%. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
240
8
32

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(289 citation statements)
references
References 9 publications
9
240
8
32
Order By: Relevance
“…She found that on average 6.5% of the students who enrolled in a MOOC met the certificate-earning criteria of the course. In a later study she found that the success rate reached a mean value of 12.6%, which entailed an average dropout rate of 87.4% (Jordan, 2015).…”
Section: Related Work On Dropout and Success In Moocsmentioning
confidence: 93%
See 1 more Smart Citation
“…She found that on average 6.5% of the students who enrolled in a MOOC met the certificate-earning criteria of the course. In a later study she found that the success rate reached a mean value of 12.6%, which entailed an average dropout rate of 87.4% (Jordan, 2015).…”
Section: Related Work On Dropout and Success In Moocsmentioning
confidence: 93%
“…However, after a short time, this first excitement was followed by frustration. Despite its popularity, the number of MOOC-takers who actually completed a MOOC after enrollment was reported to be very low with dropout rates between 98 and 90% (Jordan, 2014(Jordan, , 2015Koller, Ng, Do, & Chen, 2013;Liyanagunawardena, Parslow, & Williams, 2014;Reich, 2014). Many researchers agreed that the learning circumstances in MOOCs are exceptional (Huin, Bergheaud, Caron, Codina, & Disson, 2016;Koller et al, 2013;Liyanagunawardena et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These issues, as they relate to MOOCs, have been fully discussed and studied by numerous researchers (Lowenthal & Hodges, 2015;Rodriguez, 2012;Margaryan, Bianco, & Littlejohn, 2015;Jordan, 2015). Clearly, we are still early in the research that truly understands learner perception and attitude within the MOOC environment.…”
Section: Introductionmentioning
confidence: 99%
“…While the interactive and multimedia features of e-learning have been seen to attract the learners' attention to the learning content of the course, the retention of the initial interest and attention and the lasting engagement of the learners in the educational activities are objectives not fully conquered as yet. The impressively low percentage of learners subscribed to MOOCs, [7], that complete their courses (an average of 12% reported in 2015) is an aspect of the same problem, the MOOCs being typical examples of purely e-learning education. To address this weakness, modern e- learning platforms incorporate learning style recognition in adaptive learning platforms that can personalize both the learning content and the media through which this content is offered, [8], [9], narration, Animated Pedagogical Agents (APA), [10], [11], affective computing, [12], [13], gamification, [14], 3D or Virtual Reality environments, [15], and other such state-of-the-art technologies.…”
Section: E-learning Technologies In the Blended Learning And The Flipmentioning
confidence: 99%